Effect of preoperative sleep quality on rapid postoperative recovery from non-traumatic rotator cuff injuries - Mou, Limin; Zhang, Wenhao; Liao, Jun; Zhang, Siping; Zhao, Lingling; Aimaiti, Remila; Abuduxiku, Munire; Xiang, Wenyuan; Deng, Yingjie; Fang, Rui (Frontiers in Medicine, 2025)
BackgroundGlobal aging has led to a continuous increase in rotator cuff injuries, often accompanied by clinical-related sleep disorders. There is a lack of clinical research on whether preoperative sleep quality affects rapid postoperative recovery; therefore, it is necessary to conduct clinical follow-up studies to explore the relationship between preoperative sleep quality and postoperative rehabilitation, in order to provide rehabilitation guidance for clinical practice.MethodsIn this prospective cohort study, 256 patients who underwent arthroscopic rotator cuff repair (ARCR) at our center from January 2022 to January 2024 were grouped based on the Pittsburgh Sleep Quality Index (PSQI): the high sleep quality group (HSQG, PSQI < 7, n = 120) and low sleep quality group (LSQG, PSQI ≥ 7, n = 136). All patients were given the same rapid rehabilitation protocol. Before the operation and on the 1st, 3rd, 1st week, 1st month, 3rd month, and 6th month after the operation, visual analog scale (VAS) pain scores, Self-Rating Anxiety Scale (SAS) score, Self-Rating Depression Scale (SDS) score, American Shoulder and Elbow Surgeons (ASES) score, Constant-Murley score, and patient satisfaction were evaluated. At the same time, the occurrence of adhesions, re-tears, and other complications was recorded.ResultsAll 256 cases successfully completed arthroscopic repair and received complete follow-up. There were no statistically significant differences in baseline data, pain and function scores between the two groups (p > 0.05). Early stage: In the first day, third day and first week after surgery, the VAS, SAS and SDS scores of the HSQG were significantly lower than those of the LSQG (p < 0.05). Mid-term: At 1, 3, and 6 months after surgery, the differences in the above indicators disappeared (p > 0.05). Function: The ASES and Constant-Murley scores of the HSQG were better than those of the LSQG from 1 week to 3 months after surgery (p < 0.05), and there was no difference between the two groups at other time points. Satisfaction: The hospital satisfaction of the HSQG was significantly higher (p < 0.05). Complications: The incidence of LSQG was 5.9%, and that of high sleep quality group was 3.3%. There was no statistically significant difference (p > 0.05).ConclusionMaintaining good sleep quality before surgery can alleviate early postoperative pain, reduce the risk of postoperative anxiety and depression, accelerate functional recovery, and enhance patient satisfaction. It is recommended to incorporate preoperative sleep optimization into the rapid rehabilitation process for rotator cuff injuries to facilitate patients’ rapid postoperative recovery.